Design of controlled blasting (pre-splitting) in Golegohar iron ore mine, Iran. (March 2015) - Dindarloo, S. R.; Askarnejad, N-A.; Ataei, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Pre-splitting is a controlled blasting technique with applications in open pit mines. The main objectives of pre-splitting in open pit mining are: preventing/controlling back-break; controlling excessive ground vibrations; and filtering the effects of explosive gases from production blasting. This technique is especially effective in back-break control through providing a separating surface between the main blasting pattern and open pit final walls. In this study, a large open pit mine was the case study for the goal of designing pre-splitting through implementation of direct and cost effective experiments. Three tests were designed and performed at the mine. Back-break was successfully controlled through proper design of pre-splitting based on the results of the experiments.